IMPACT OF NON-OIL REVENUE ON GOVERNMENT BUDGET IMPLEMENTATION IN NIGERIA (1999-2022) - Akombende, Udie Jacob; Chukwu, U.C. (EBSU Journal of Social Sciences and Humanities, 2024)
The study examined the impact of non-oil revenue on government budget implantation in Nigeria. Specifically, the study sought to evaluate the impact of agricultural revenue, custom and excise duty, mining revenue, company income tax and value added tax on government budget implantation in Nigeria. The study adopted ex-post facto research design which enabled data to be collected from Central Bank of Nigeria (CBN) Statistical Bulletin and annual reports and accounts of Federal Inland Revenue Service (FIRS) for the period of 23 years, spanning from 1999 to 2022. The first preliminary test conducted in the study was unit root test using the conventional Augmented Dickey-Fuller (ADF) Statistics on both the independent and dependent variables. The aim of the unit root test was to validate the data used in the analysis of the study in order to avoid spurious regression results. Descriptive statistics was performed to ascertain the characteristics of the model variables. The study went further and conducted Correlation Matrix Test so as to determine the strength and magnitude of the impact of the independent variables on government budget implantation in Nigeria. Ordinary Least Square (OLS) Multiple Regression Model was adopted to determine the empirical relationship between components of non-oil revenue and government budget implementation at 0.05 level of significance. The results of the regression analysis revealed that agricultural revenue, custom and excise duty, company income tax and value added tax had positive and significant impact on government budget implantation in Nigeria. However, the study also observed that mining revenue had positive and no significant impact on government budget implantation in Nigeria. The implication of these results is that non-oil revenue has contributed positively in the implementation of government budget in Nigeria. The study therefore recommended that government should channel efforts towards creating international awareness on the business and investment opportunities available in Nigeria in non-oil areas such as agricultural, solid mineral and industrialization.